Expression patterns of Phf5a/PHF5A and Gja1/GJA1 in rat and human endometrial cancer - Falck, Eva (BioMed Central, 2013)
Endometrial adenocarcinoma is the most frequently diagnosed cancer of the female genital tract in the western world. Studies of complex diseases can be difficult to perform on human tumor samples due to the high genetic heterogeneity in human. The use of rat models is preferable since rat has similarities in pathogenesis and histopathological properties to that of human. A genomic region including the highly conserved Phf5a gene associated to development of EAC has previously been identified in an association study. PHF5A has been suggested to acts as a transcription factor or cofactor in the up regulation of expression of Gja1 gene in the presence of estrogen. It has earlier been shown that the Phf5a gene is down regulated in rat EAC derived cell lines by means of expression microarrays. We analyzed the expression of Phf5a and Gja1 by qPCR, and potential relations between the two genes in EAC tumors and non-malignant cell lines derived from the BDII rat model. In addition, the expression pattern of these genes was compared in rat and human EAC tumor samples. Changes in expression for Phf5a/PHF5A were found in tumors from both rat and human even though the observed pattern was not completely consistent between the two species. By separating rat EAC cell lines according to the genetic background, a significant lower expression of Phf5a in one of the two cross backgrounds was revealed, but not for the other. In contrast to other studies, Phf5a/PHF5A regulation of Gja1/GJA1 was not revealed in this study.